Validation of Malay-Adapted Nordic Occupational Skin Questionnaire (NOSQ-2002/SHORT) as a reliable and specific screening tool for occupational skin diseases - A. Rahman, Nor Azlina; Mohd Roze, Amalina; Razali, Ailin; Samsuddin, Niza; Syed Jamaludin, Mohd Shaqif; Yusof, Muhammad Zubir; Nik Mohamed, Nik Mohamed Nizan; Nik Mahmod, Nik Ahmad Kamal; Abdullah Hair, Nor Ahmad Fitri; Hullon, Rajinderjit Singh (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2023)
Occupational skin disease is one of the most reported occupational diseases. Its prevention is important to ensure good health and quality of life of workers which can be achieved through screening, for which the Nordic Occupational Skin Questionnaire, NOSQ-2002/SHORT was developed. The questionnaire had been adapted and translated into Malay Language for use in Malaysia and other Malay-speaking communities. A cross-sectional pilot study was carried out to check the validity and reliability of the Malay-adapted NOSQ-2002/SHORT, using purposive sampling among a few factory workers in East-Coast Malaysia. The results showed that the finalized version of the Malay-adapted questionnaire has good validity and reliability, with the Cronbach alpha of 0.867. The specificity and negative predictive values were quite high, with the values of 86.0% (95% CI: 80.1, 90.8) and 96.9% (95% CI: 93.6, 98.5), respectively. Even though the sensitivity and positive predictive values were a bit lower at 72.2% (95% CI: 46.5, 90.3) and 34.2% (95% CI: 24.7, 45.2), respectively, it is still higher than previously reported questionnaire used to screen skin condition. In conclusion, the Malay adapted NOSQ-2002/SHORT is valid and reliable as a screening tool for occupational skin diseases, in which it is inexpensive, simple, and quick to be used.